1998
DOI: 10.1126/science.280.5364.708
|View full text |Cite
|
Sign up to set email alerts
|

A Trivalent System from Vancomycin· d -Ala- d -Ala with Higher Affinity Than Avidin·Biotin

Abstract: Tris(vancomycin carboxamide) binds a trivalent ligand derived from D-Ala-D-Ala with very high affinity: dissociation constant (Kd) approximately 4 x 10(-17) +/- 1 x 10(-17) M. High-affinity trivalent binding and monovalent binding are fundamentally different. In trivalent (and more generally, polyvalent) binding, dissociation occurs in stages, and its rate can be accelerated by monovalent ligand at sufficiently high concentrations. In monovalent binding, dissociation is determined solely by the rate constant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
195
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(202 citation statements)
references
References 21 publications
5
195
0
2
Order By: Relevance
“…This phenomenon has a natural basis, vital to the function of binding proteins such as IgM with 10 binding sites (39) or the biological adhesion of many viruses (40), and even the extracellular matrix is polyvalent (41). Polyvalency is used frequently in the design of synthetic bioactive molecules to enhance their binding strength and has been used in the creation of bioactive peptides, organic molecules, carbohydrates, nucleotides, antibiotics, and phage mimics, among others (42)(43)(44)(45)(46). Polyvalency has even been explored for biological signaling initiated by receptor dimerization, as is the case for VEGF receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has a natural basis, vital to the function of binding proteins such as IgM with 10 binding sites (39) or the biological adhesion of many viruses (40), and even the extracellular matrix is polyvalent (41). Polyvalency is used frequently in the design of synthetic bioactive molecules to enhance their binding strength and has been used in the creation of bioactive peptides, organic molecules, carbohydrates, nucleotides, antibiotics, and phage mimics, among others (42)(43)(44)(45)(46). Polyvalency has even been explored for biological signaling initiated by receptor dimerization, as is the case for VEGF receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of substantially higher affinity due to multivalency was elegantly demonstrated in studies using monovalent and trivalent vancomycin and D-Ala-D-Ala derivatives. These studies showed that dissociation constant of monovalent vancomycin and monovalent D-Ala-DAla is Ϸ10 Ϫ6 M, whereas the dissociation constant of the trivalent vancomycin and trivalent D-Ala-D-Ala is 10 Ϫ17 M (25). The structure presented here shows that the LC sites can bind two IC peptide fragments simultaneously.…”
mentioning
confidence: 68%
“…They have proposed that these derivatives have enhanced avidity for D-Ala-D-Lac moieties presented on bacterial cell surfaces because the interactions are effectively divalent (40). There is considerable biophysical data to support the hypothesis that lipid-substituted glycopeptides have enhanced avidity for both D-Ala-D-Ala-and D-Ala-D-Lacmodified surfaces (41), and it has also been shown that covalent dimers and trimers of vancomycin bind covalent multimers of D-Ala-D-Ala many orders of magnitude better than the monomers bind (42). Nevertheless, there is no evidence that chlorobiphenyl vancomycin derivatives kill vanA strains by dimerizing near cell surfaces and binding D-Ala-D-Lac (43,44).…”
Section: Discussionmentioning
confidence: 99%